Preparation and physicochemical properties of konjac glucomannan ibuprofen ester as a polysaccharide-drug conjugate. Issue 1 (16th September 2020) - Kang, Huiting; Guan, Lianxiong; An, Kai; Tian, Dating
Abstract: A novel drug-polysaccharide conjugate with konjac glucomannan (KGM) as a drug carrier was fabricated through the esterification of ibuprofen (IBU), an anti-inflammatory drug, with KGM. The influences of the reaction conditions, such as the amount of ibuprofen acryl chloride, reaction time, reaction temperature, and the amount of catalyst, on the degree of substitution were investigated. KGM ibuprofen ester (KGM-IBU) was characterized by Fourier transform infrared spectrometry (FTIR), X-ray diffraction (XRD), solid-state 13 C NMR, scanning electron microscopy (SEM), transmission electron microscopy (TEM), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and dynamic mechanical analysis (DMA). The hydrophobic structure of IBU in KGM-IBU was proven by the fluorescence emission spectra of pyrene. In addition, by using commercially available ibuprofen sustained-release capsules (IBU-SRC) as a control, the in vitro controlled release performance of KGM-IBU was evaluated. The cumulative release of IBU-SRC within 36 h was 94%, while that of KGM-IBU within 36 h was 77%. The results showed that KGM-IBU had better sustained-release performance without a burst release effect. The obtained products could be used as a potential biocompatible sustained-release drug delivery system. Graphical Abstract: